Live birth from a patient with a threeway balanced translocation t5 8 12 - Anil Ramdeo; Kinnon Naidoo; Teresa Ernest; Katarzyna Pluta (South African Medical Association, 2015)
Background: Three-way balanced translocations are unusual and can lead to infertility as well as abnormal embryos. In this case report we describe a couple that experienced repeated miscarriages due to the male partner being a carrier of a three-way translocation t(5, 8, 12) . Objectives: Array comparative genomic hybridization (array-CGH) was used to screen embryos for chromosome imbalances. Methods: Embryo biopsy, preimplantation genetics diagnosis (PGD) using 24Sure+ kit to detect translocations in embryos. Results: Out of 10 embryos tested, 2 were found to be unbalanced translocation carriers, 4 were aneuploid, 2 failed to amplify and 2 were euploid. Transfer of 2 euploid embryos resulted in a singleton pregnancy and subsequently a birth of a baby. Conclusion: Array-CGH in conjunction with 24Sure+ kit should be used as a routine screening method for embryos of balanced translocation carriers as it can decrease the time to pregnancy and prevent repeated miscarriages.